Optimization Analysis of Vegetable Farming with Hydroponic System in Kendari City (Case Study of Simbo Hydroponics) - Mustadin; Iswandi, R. Marsuki; Rosmawaty (International journal of technology and education research, 2025)
This study aims to analyze the optimal use of production resources in hydroponic vegetable farming in order to maximize income. The research was conducted from February to July 2025. The method used in this study is linear programming analysis using the simplex method, assisted by the POM-QM for Windows IV software to determine the optimal combination of resources, including seeds, nutrients, and labor. The results showed that the use of production resources had reached an optimal condition, with full utilization of nutrients (70 liters) and labor (8 man-days). The resources that remained in surplus and were not limiting factors included lettuce seeds, pakcoy seeds, caisim seeds, samhong seeds, and kailan seeds. Among the five crops, pakcoy still had potential for further optimization, while the other four had already reached optimal levels. Each type of vegetable showed that production quantity matched demand (optimal). The optimal production levels for each crop were: lettuce 60 kg, pakcoy 120.63 kg, caisim 30 kg, samhong 30 kg, and kailan 90 kg. The total optimal income obtained from this combination amounted to IDR 10,201,148 per production cycle